PENERAPAN PEMBELAJARAN BERBASIS PROYEK BERBASIS KEARIFAN LOKAL JAMBI UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Lubis, Ali Musa; Jamilah, Jamilah; Rapiko, Rapiko (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to describe the implementation of Project-Based Learning (PjBL) based on Jambi local wisdom in Islamic Religious Education (IRE) courses and to analyze its impact on students' critical thinking skills. The research method used was classroom action research (CAR) conducted in two cycles involving 32 students as research subjects. Data collection instruments included observation sheets, critical thinking tests, and documentation. The results showed that the implementation of PjBL based on Jambi local wisdom improved students' critical thinking skills, as indicated by the increase in average scores on analysis, evaluation, and synthesis indicators. This indicates that the integration of local wisdom into IRE learning provides contextual learning experiences, fosters awareness of local culture, and enhances students' critical thinking skills.